Kesabaran (Al-Ṣabr) dalam Al-Qur'an: Analisis Interpretasi Tematik, Semantik, dan Kontekstual - Nurwahid Syam; Muhmmad Yusuf; Mardan Mardan (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2026)
This article examines the concept of al-ṣabr in the Qur'an using a qualitative approach based on literature studies with the method of thematic interpretation (tafsīr mawḍū'ī). The research data is in the form of 90 verses of the Qur'an that contain the word "ṣabr" and all its derivations, both lexically and semantically. The analysis was carried out through a thematic, semantic, and balāghah approach by paying attention to the context of asbāb al-nuzūl and the Makkiyah–Madaniyah period. The results of the study show that al-ṣabr is a multidimensional ethical concept that includes spiritual, psychological, and social dimensions. In the Makkiyah period, al-ṣabr functioned as the foundation of faith resilience and individual self-control, while in the Madaniyah period, it developed into the principles of collective ethics and the social resilience of the ummah. These findings confirm that al-ṣabr in the Qur'an is not a passive attitude but an active ethical value that plays an important role in the formation of a religious personality and a resilient Islamic society.